STRATEGI BIDANG PENGELOLAAN ASET BADAN KEUANGAN DAERAH DALAM PROSEDUR PENGHAPUSAN BARANG MILIK DAERAH DI KOTA DEPOK TAHUN 2020. - Faricha Rizki (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
The importance of awareness of the management of regional property is increasing with the improvement of regulations at the central and regional levels, the management of regional property covers all scopes from planning needs and budgeting, procurement, use, utilization, security, and asset preservation, transfer, destruction or elimination, administration and guidance as well as supervision and control. This study uses qualitative research methods using interview, documentation and observation data collection techniques. The results of this study indicate that the management of regional assets has a strategy in the elimination of regional assets by following the applicable laws and regulations